Tax Avoidance and Dividend Policy: Evidence from Indonesian State-Owned Enterprises - Randy Kuswanto (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
This study aimed to investigate the relationship between tax avoidance and dividend policy with focus on state-owned enterprises (SOEs), in Indonesia. The populations are all Indonesian firms (SOEs and non-SOEs) listed in LQ-45 index. Samples were selected using purposive sampling method. Number of collected samples are 60 firms or 118 firm-year observations (2018, 2019, and 2021). Using Moderated Regression Analysis (MRA), this study found a positive association between effective tax rate and dividend yield for non-SOEs. The result also reveals that SOEs tend not to engage in aggressive tax avoidance, with an average effective tax rate of 19.9%. Therefore, if SOEs plan to manage their taxes to lower the effective tax rate, they may provide higher yield to shareholders compared to non-SOEs.